2018
DOI: 10.1002/jlb.5ru0718-288r
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor and T-cell interactions during alloimmune inflammation in transplantation

Abstract: Complement factor and T‐cell signaling during an effective alloimmune response plays a key role in transplant‐associated injury, which leads to the progression of chronic rejection (CR). During an alloimmune response, activated complement factors (C3a and C5a) bind to their corresponding receptors (C3aR and C5aR) on a number of lymphocytes, including T‐regulatory cells (Tregs), and these cell‐molecular interactions have been vital to modulate an effective immune response to/from Th1‐effector cell and Treg acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 187 publications
(568 reference statements)
0
9
0
Order By: Relevance
“…As reported earlier, C3 in the first major active fragment, which has been reported to initiate microvascular associated injuries through the graft vascular-endothelial deposition [5,9,13,15,37,63]. In addition, endothelial deposition of C3 leads to the onset of vascular leakiness, microvascular congestion, thrombus formation, pulmonary edema and neutrophilic invasion of the microvasculature through the interaction of various inflammatory cells [15,64].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…As reported earlier, C3 in the first major active fragment, which has been reported to initiate microvascular associated injuries through the graft vascular-endothelial deposition [5,9,13,15,37,63]. In addition, endothelial deposition of C3 leads to the onset of vascular leakiness, microvascular congestion, thrombus formation, pulmonary edema and neutrophilic invasion of the microvasculature through the interaction of various inflammatory cells [15,64].…”
Section: Discussionmentioning
confidence: 69%
“…Herein, we demonstrated that early hypoxic state favors a cell-mediated inflammation, which proportionally triggers the downregulation of CD55, and thereby augments the uncontrolled release of active-C3, and Caspase-3 deposition on graft vascular endothelial cells. As reported in previous preclinical studies, alloimmune inflammation is characterized by a massive T cell infiltration (CD4 + and CD8 + ), associated proinflammatory cytokines, vascular deposition of CTL mediated Caspase-3 activation, which mutually take part in tissue and microvascular damage [9,15,37]. Our preliminary results also demonstrated a significant increase in early activation of HIF-1α mRNA (d6), followed by a massive increase in T cell infiltration and major proinflammatory cytokines (IL-2 and TNFα) during microvascular deterioration.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Tregs are potent immunosuppressive cells that are key in maintaining the homeostatic balance during dysregulated immune responses, which is a critical feature of asthma inflammation [69][70][71][72][73][74]. Tregs are generated in the thymus as a functionally mature T cell subset and in the periphery of naive T cells and are crucial in maintaining immunological unresponsiveness to self-antigens, and suppressing heightened immune responses destructive to the tissue during asthma inflammation [12,69,[75][76][77][78][79][80][81][82][83]. Tregs play a vital role in modulating and regulating immune responses by establishing the phase of immunotolerance and negating toxic inflammatory reactions, which are essential to maintain routine tissue repair as seen in several preclinical and clinical studies [60,62,84].…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Immunotolerance is a major immunological phase, which facilitates reparative microenvironment during transplantation, and plays a vital role to suppress alloimmune responses. A number of therapeutic options have been investigated to increase the number of regulatory T cells (Tregs) during allograft rejection, for example, through C5a blockade, stem cell therapy, and immune checkpoints, which potentially suppress infiltration of CD4 + T cells and antibody-mediated complement activation on vascular endothelial cells [1, 2, 48]. Cell-mediated immunotherapy is emerging as an alternative in single and combination therapies to rescue rejecting transplants.…”
Section: Introductionmentioning
confidence: 99%